La imagen: Mímesis & Méthexis - Nancy, Jean-Luc (Escritura e Imagen, 2006)
Each one of the arts constitutes the invention or the intensification of a primary sense by exclusion of other senses: In this way, the primary sense brings in its order an evocation of others which we can call a contrasted approximation: the image does resound in her sonority of mutism (for example, when in music, does in its way, refract in her a visuality of the invisibility). This general axioma of the arts justifies and disqualifies in the same gesture every tentative of “correspondence”, and at the same time does fail in advance every trap of a “total art”. If there is something like that as beginning of the art, this is its irreducible not totality: but a principal corollary opens between the arts an endless mutual resound. The image in its way operates the implication of these old notions, Mimesis and Methexis, one into the other, in a way that they can not be given to be separate. There is no mimesis, because, it does not resound with a kind of tone, in the far participation where the shape comes.